Cellular Mechanisms for Dopamine D(4) Receptor-induced Homeostatic Regulation of α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid (AMPA) Receptors - Yuen, Eunice Y. (American Society for Biochemistry and Molecular Biology, 2011)
Aberrant dopamine D(4) receptor function has been implicated in mental illnesses, including schizophrenia and attention deficit-hyperactivity disorder. Recently we have found that D(4) receptor exerts an activity-dependent bi-directional regulation of AMPA receptor (AMPAR)-mediated synaptic currents in pyramidal neurons of prefrontal cortex (PFC) via the dual control of calcium/calmodulin kinase II (CaMKII) activity. In this study, we examined the signaling mechanisms downstream of CaMKII that govern the complex effects of D(4) on glutamatergic transmission. We found that in PFC neurons at high activity state, D(4) suppresses AMPAR responses by disrupting the kinesin motor-based transport of GluR2 along microtubules, which was accompanied by the D(4) reduction of microtubule stability via a mechanism dependent on CaMKII inhibition. On the other hand, in PFC neurons at the low activity state, D(4) potentiates AMPAR responses by facilitating synaptic targeting of GluR1 through the scaffold protein SAP97 via a mechanism dependent on CaMKII stimulation. Taken together, these results have identified distinct signaling mechanisms underlying the homeostatic regulation of glutamatergic transmission by D(4) receptors, which may be important for cognitive and emotional processes in which dopamine is involved.